Fire Detection and Distance Measurement Based on Infrared Sensors and Internet of Things (IoT) - Decky Ari Irwanto; Jaine Faleri Nona; Irawati Dewi Syahwir; Dewi Setiawati (Ali Institute of Research and Publication, 2026)
This research was motivated by the need for a fire detection system capable of detecting the presence of fire while providing real-time fire distance information that has the potential to be applied in automatic fire extinguishing systems. The result of this study is a prototype of a fire detection and distance measurement system based on the YG1006 infrared sensor integrated with the Internet of Things (IoT). The method used was an experimental approach through hardware and software design using ESP32, the HX711 module as a 24-bit Analog-to-Digital Converter (ADC), and transistor-based signal amplification. The results showed that the system was able to distinguish between the presence and absence of fire with an ADC threshold value of 1000 and measure fire distance up to 250 cm. The logarithmic regression model used had a coefficient of determination of 0.9949 with a maximum absolute error of 9% within the range of 60–250 cm. The system was also capable of real-time monitoring through Google Spreadsheet. The accuracy of fire distance measurement decreased when the fire was positioned very close to the sensor, specifically at distances less than 60 cm, due to sensor saturation.